2009
DOI: 10.1007/s10562-009-9991-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Catalyst Deactivation in the Oxidative Dehydrogenation of n-Butene to 1,3-Butadiene over Zn-Ferrite Catalysts

Abstract: An efficient method to enhance the catalytic properties of Zn-ferrite catalyst in the oxidative dehydrogenation of n-butene to 1,3-butadiene is proposed. The incorporation of phosphorous compound in Zn-ferrite is very effective to improve the catalytic activity as well as to maintain extremely long useful lives at high oxygen to n-butene ratio. It is found that the amount of phosphorous is critical and the presence of appropriate amount of phosphorous in catalyst may contribute the catalyst stabilization by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…As shown in Table 2, the crystallite sizes of Ni x Fe 3-x O 4 samples are in the range of 33-61 nm, demonstrating the efficacy of the proposed method to produce nano-size spinel Ni x Fe 3-x O 4 . In relation with the Ni contents, it was found that increased Ni-content from x = 0.2 to x = 0.6) resulted in increased particle size of the spinel NiFe 2 O 4 crystalline phase from around 34 to 61 nm.…”
Section: X-ray Diffraction Analysismentioning
confidence: 73%
See 1 more Smart Citation
“…As shown in Table 2, the crystallite sizes of Ni x Fe 3-x O 4 samples are in the range of 33-61 nm, demonstrating the efficacy of the proposed method to produce nano-size spinel Ni x Fe 3-x O 4 . In relation with the Ni contents, it was found that increased Ni-content from x = 0.2 to x = 0.6) resulted in increased particle size of the spinel NiFe 2 O 4 crystalline phase from around 34 to 61 nm.…”
Section: X-ray Diffraction Analysismentioning
confidence: 73%
“…Ferrite compounds with spinel structure have attracted major attention due to their suitable properties for diverse technological applications, such as electronic devices [1][2], magnetic storages [3], and catalysis [4][5]. In general, the applications of this type of compound are governed by peculiar properties, which in turn depends on the chemical composition and microstructure [3,6].…”
Section: Introductionmentioning
confidence: 99%
“…Various complex metal oxides, and metal oxides or metal‐supported catalysts, have been investigated for the ODH of many hydrocarbons, including propane, ethylbenzene, ethane, n‐butane, n‐butene, and cyclohexane . For the ODH of n‐butene and n‐butane, Pt−In catalyst, ferrite‐type catalysts,, V‐containing catalysts, Bi−Mo catalysts, and the CuO/Al 2 O 3 catalyst exhibited high activity.…”
Section: Introductionmentioning
confidence: 99%
“…Among various catalysts, zinc ferrite‐type catalysts such as Zn−Fe,,,, Zn−Fe‐Cr, and Zn−Fe‐Al have been widely studied for the ODH of the C4 fraction. For example, it was reported that a zinc ferrite catalyst that was modified by heteropoly acid or sulfonic acid showed good performance for the ODH of but‐1‐ene ,.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation